Amplifying and affirming students' voices through CALS-informed instruction. Issue 1 (2nd January 2020) - Uccelli, Paola; Phillips Galloway, Emily; Aguilar, Gladys; Allen, Melanie
ABSTRACT: Recent literacy research calls for pedagogical approaches that multiply students' opportunities to discuss texts and ideas that matter. We argue that understanding mid-adolescents' language needs can further inform discussion-based approaches. Our assessment research reveals that substantial differences in Core Academic Language Skills (CALS) – high-utility school-relevant language skills – help explain why comprehending school texts can be challenging for many adolescents. Our research with Latinx dual language learners' and their teachers documents how leveraging heritage languages and identities contributes to academic success. Integrating insights from our teacher-researcher collaborations, we call for practices and dispositions that amplify language resources and awareness and affirm students' voices by engaging teachers and students in reflecting about language, context, and power while scaffolding CALS across content areas and grades. Affirming while amplifying students' voices entails expanding students' and teachers' critical rhetorical flexibility, the ability to use language critically and flexibly for particular contexts and purposes.